Academic Collaboration in the Era of Globalization: an Analysis of the Impact of Digitalization on Early Childhood Education - Jami'atul Hasanah; Khoridatul Azizah (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2026)
This study investigates the role of academic collaboration in improving the quality of early childhood education (ECE) amid the rapid digitalization brought by globalization. The main focus lies in understanding how collaborative academic networks enhance educators’ competencies, expand knowledge sharing, and stimulate innovation in technology-based learning. Using a literature review method, this research examines journals, books, and scholarly publications related to global education and digital literacy in ECE. The findings reveal that academic collaboration plays a crucial role in fostering teacher professionalism and integrating digital tools effectively in early learning settings. However, digitalization also presents challenges such as decreased social interaction among children and increased dependence on digital devices. The study concludes that strengthening academic collaboration serves as a strategic approach to maximize the benefits of digital learning while mitigating its negative impacts on young children’s holistic development in the era of globalization.